Should Investors in Commodity Markets Be Superstitious (Based on the Example of 29 Commodities)? - Borowski, Krzysztof (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The issue of efficiency of financial markets has always fascinated scientists. It is significant from the point of view of assessing portfolio management effectiveness and behavioural finance. In the first part of this paper, the hypothesis of the unfortunate dates effect was tested upon 29 commodity prices in relation to the following four approaches: close‑close, overnight, open‑open, and open‑close. The rates of return were calculated for the sessions falling on the 13th and 4th day of the month, Friday the 13th and Tuesday the 13th. The study proved the occurrence of seasonal effects on the so‑called unlucky dates.